Epithelioid Hemangioendothelioma in the Tongue: A Rare Case Report - Deniz SURMELI CIRKIN; Ilke Evrim SECINTI; Esin DOGAN; Gul SOYLU OZLER (Federation of Turkish Pathology Societies, 2023)
Epithelioid hemangioendothelioma is a rare malignant vascular neoplasm caused by the proliferation of neoplastic endothelial cells. Epithelioid hemangioendothelioma may develop in any organ, but it is commonly observed in the extremities. The tongue is a very unusual location for epithelioid hemangioendothelioma. A 55-year-old male patient presented to the outpatient head and neck clinic with lumps in the tongue, pain, and limitation of motion. The polypoid mass detected in the anterior midline of the tongue was excised. Microscopically, the tumor cells included slightly pleomorphic oval or round vesicular nuclei with an eosinophilic cytoplasm that variably contained vacuoles. There were 4 mitoses per 10 high power fields and there was no necrosis. In immunohistochemical study, the tumor cells were positively stained with CD31 and CD34 whereas they were negatively stained with TFE3, SMA, S-100, HHV-8 and EMA. The patient was diagnosed with "epitheloid hemangioendothelioma". Only ten cases have been reported in the tongue in the literature. Our case was the eleventh case, and we aimed to report this case as a rare entity with an unusual location.